Changes in the degree of lateral root trait plasticity and trade-offs of maize under long-term no tillage - Yin, Liming; Lv, Qiushuang; Wang, Peng; Xie, Hongtu (Frontiers in Plant Science, 2024)
While no tillage (NT) can significantly influence soil structure stratification compared to conventional tillage (CT), a comprehensive understanding of the degree of root trait plasticity and trade-offs of lateral roots of crops at various growth stages along a deep soil profile in response to NT remains elusive. This knowledge gap is important for understanding soil resource acquisition strategies and yield of crops. We systematically investigated the traits of lateral roots at jointing and flowering stages in a long-term (12 years) experiment in Northeast China where maize (Zea mays) has been continuously planted under CT and NT with or without maize residue mulch on soil surface. We also measured soil penetration resistance and bulk density. Soil penetration resistance was reduced at the jointing stage, and was increased at the flowering stage under NT especially at a depth of 10 -40 cm. Root length density decreased under NT across the two growth stages by on average 22%. In contrast, specific root length and diameter showed greater plasticity, ranging from -14% to 20% and from -11% to 8%, respectively, relative to those under CT. These responses could be attributed to changes in root length proportions with different diameters associated with differences in soil penetration resistance between tillage practices. The negative relationships between root traits were stronger under CT than NT, and became weaker from the jointing stage to the flowering stage. To the best of our knowledge, for the first time, our study provides empirical evidence for pivotal root trait plasticity and trade-offs across growth stages as key indicators of changes in soil structure and resources in response to NT. These insights contribute to a better understanding of a potential shift in soil resource acquisition strategies of crops under NT.